PERILAKU KEAGAMAAN PESERTA DIDIK DALAM KELUARGA BROKEN HOME (Studi Kasus Siswa Berlatar Belakang Keluarga Broken Home di SMKN 1 Lamongan) - Nafaidatus Sholihah; Winarto Eka Wahyudi (Universitas Islam Lamongan, 2020)
This article discusses religious behavior in students who have broken home family backgrounds. Religious behavior is a statement or expression of human mental life that is measured, calculated and studied which is manifested in the form of words, actions or physical actions related to the experience of the teachings of Islam. This research is motivated by the number of students who have broken home family backgrounds who are still not good in terms of courtesy and worship. The results of this study include the following findings: first, worship of students who have broken home family backgrounds results are not good because there are differences in the background of each parent who does not pay attention to their children's worship. Secondly, the manners of students who have broken home family backgrounds show poor behavior due to neglect and neglect of parents' attention to children's character education.